Christmas with Dad - McCormack, Conor (Clarity Productions Ltd., 2008)
Verzio FF Submission Duration: 00:12:00 AJ's tough exterior conceals a sensitive young man, living through some of the defining moments in his life. The family home is full of noise and conflict as seven children compete for space, but amid the chaos young lives are forming. Filmed entirely within the physical setting of home, "Christmas with Dad" follows this most unusual family as they prepare for the festive season and ready themselves for the arrival of an eighth child. With remarkable access and insight, the film reveals a young man struggling to define his role as father, haunted by his own childhood and facing up to a very uncertain future.